2014
DOI: 10.1097/scs.0000000000000936
|View full text |Cite
|
Sign up to set email alerts
|

Septal Cartilage Plug Technique in Spontaneous Cerebrospinal Fluid Rhinorrhea Postoperatively Diagnosed With Partial Empty Sella Syndrome

Abstract: The otolaryngologist should consider empty sella syndrome for diagnostic guidance when evaluating patients with nontraumatic spontaneous cerebrospinal fluid (CSF) rhinorrhea. The radiographic finding of empty sella is frequently reported in patients with benign intracranial hypertension (BIH). Patients who have a spontaneous CSF leak in the absence of florid symptoms of BIH may have a disrupted pattern of CSF flow, and because they are actively leaking CSF before surgical repair, they may be at risk for develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Many authors indicated the reliable use of the cartilage graft in the anterior skull base defect repair with minor infectious complication rates [24, 25]. However, the studies with the cartilage graft concerning the lateral skull base are relatively limited.…”
Section: Discussionmentioning
confidence: 99%
“…Many authors indicated the reliable use of the cartilage graft in the anterior skull base defect repair with minor infectious complication rates [24, 25]. However, the studies with the cartilage graft concerning the lateral skull base are relatively limited.…”
Section: Discussionmentioning
confidence: 99%